PERANAN ORANG TUA: PENGENALAN AKAN ALLAH SEJAK USIA DINI BERDASARKAN ULANGAN 6:4-7 - Yuliana Yuli Tan; Rikardo P. Sianipar (The Way: Jurnal Teologi dan Kependidikan, 2023)
The aim of this research is to determine the role of parents in introducing God from an early age based on Deuteronomy 6:4-7 and its implications for spiritual growth. Considering the important role of parents in educating, especially early childhood, which is a golden period for growth and character formation, it is necessary to introduce God to them so that they have a strong foundation for their spiritual growth in the future. The condition of teenagers is still unstable, they are easily influenced by their social environment and become involved in delinquency. It is the responsibility of parents to introduce God, teach them to love Him so that faith in Him grows and bears fruit. This research uses descriptive qualitative analytical methods with data collection procedures using observation and interviews. Data analysis techniques, namely reducing and presenting data and researchers interpreting it. The results of the research are that there are parents who educate their children using violence but also with love; Examples given in everyday life and providing guidance. The conclusion is that parents at GBI True Vine Jakarta carry out their role in educating, setting an example, and guiding their children. Showing faith in God, introducing His love. The spirituality of teenagers at GBI True Vine Jakarta grows as they get older, they have faith in Jesus and have a desire to do their best for Him.